Does the sight of physical threat induce a tactile processing bias? Modality-specific attentional facilitation induced by viewing threatening pictures. - Van Damme, S; Gallace, A; Spence, C; Crombez, G; Moseley, G (2009)
Threatening stimuli are thought to bias spatial attention toward the location from which the threat is presented. Although this effect is well-established in the visual domain, little is known regarding whether tactile attention is similarly affected by threatening pictures. We hypothesised that tactile attention might be more affected by cues implying physical threat to a person's bodily tissues than by cues implying general threat. In the present study, participants made temporal order judgments (TOJs) concerning which of a pair of tactile (or auditory) stimuli, one presented to either hand, at a range of inter-stimulus intervals, had been presented first. A picture (showing physical threat, general threat, or no threat) was presented in front of one or the other hand shortly before the tactile stimuli. The results revealed that tactile attention was biased toward the side on which the picture was presented, and that this effect was significantly larger for physical threat pictures than for general threat or neutral pictures. By contrast, the bias in auditory attention toward the side of the picture was significantly larger for general threat pictures than for physical threat pictures or neutral pictures. These findings therefore demonstrate a modality-specific effect of physically threatening cues on the processing of tactile stimuli, and of generally threatening cues on auditory information processing. These results demonstrate that the processing of tactile information from the body part closest to the threatening stimulus is prioritized over tactile information from elsewhere on the body.